Characteristics of immune checkpoint inhibitor-induced encephalitis and comparison with HSV-1 and anti-LGI1 encephalitis: A retrospective multicentre cohort study. (November 2022) - Müller-Jensen, Leonie; Zierold, Sarah; Versluis, Judith M.; Boehmerle, Wolfgang; Huehnchen, Petra; Endres, Matthias; Mohr, Raphael; Compter, Annette; Blank, Christian U.; Hagenacker, Tim; Meier, Friedegund; Reinhardt, Lydia; et al.
Abstract: Aim: Immune checkpoint inhibitor-induced encephalitis (ICI-iE) is a rare but life-threatening toxicity of immune checkpoint inhibitor treatment. We aim to identify the characteristics of ICI-iE and describe factors that discriminate it from herpes simplex virus (HSV)-1 encephalitis and anti-leucine-rich glioma-inactivated 1 (anti-LGI1) encephalitis, as two alternative entities of encephalitis. Methods: In this retrospective multicentre cohort study, we collected patients with ICI-iE reported to the Side Effect Registry Immuno-Oncology from January 2015 to September 2021 and compared their clinical features and outcome with 46 consecutive patients with HSV-1 or anti-LGI1 encephalitis who were treated at a German neurological referral centre. Results: Thirty cases of ICI-iE, 25 cases of HSV-1 encephalitis and 21 cases of anti-LGI1 encephalitis were included. Clinical presentation of ICI-iE was highly variable and resembled that of HSV-1 encephalitis, while impairment of consciousness (66% vs. 5%, p = .007), confusion (83% vs. 43%; p = .02), disorientation (83% vs. 29%; p = .007) and aphasia (43% vs. 0%; p = .007) were more common in ICI-iE than in anti-LGI1 encephalitis. Antineuronal antibodies (17/18, 94%) and MRI (18/30, 60%) were mostly negative in ICI-iE, but cerebrospinal fluid (CSF) showed pleocytosis and/or elevated protein levels in almost all patients (28/29, 97%). Three patients (10%) died of ICI-iE. Early immunosuppressive treatment was associated with better outcome (r = 0.43). Conclusions: ICI-iE is a heterogeneous entity without specific clinical features. CSF analysis has the highest diagnostic value, as it reveals inflammatory changes in most patients and enables the exclusion of infection. Early treatment of ICI-iE is essential to prevent sequelae and death. Highlights: Presentation of ICI-iE is variable and resembles that of HSV-1 encephalitis. Abnormal MRI and antineuronal antibodies are less common than previously reported. Analysis of cerebrospinal fluid has the highest diagnostic value in ICI-iE. ICI-iE has a mortality of 10% and long-term sequelae occur in 47% of patients. Early immunosuppressive treatment of ICI-iE is associated with full recovery.